2019
DOI: 10.1109/access.2019.2921802
|View full text |Cite
|
Sign up to set email alerts
|

Photonics-Based High-Resolution 3D Inverse Synthetic Aperture Radar Imaging

Abstract: A photonics-based radar for high-resolution 3D microwave imaging is proposed and demonstrated, in which high range resolution is achieved by employing a wideband linearly frequency modulated signal, and high cross-range resolution in both azimuth and elevation is realized by rotating the target around two orthogonal axes to compose a 2D inverse synthetic aperture. The proposed radar performs photonics-based in-phase/quadrature up-conversion and de-chirp processing in the transmitter and receiver, respectively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 28 publications
(30 reference statements)
1
11
0
Order By: Relevance
“…It is confirmed that the IF-band signal quadrupling by the DPMZM was successful. If the IF signal with a higher center frequency and wider bandwidth can be applied to the DPMZM using a state-of-the-art AWG, the center frequency and the bandwidth of the quadrupled signal can be higher and wider, similar to previous studies in References [11,12,[21][22][23].…”
Section: Experimental Setup and Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…It is confirmed that the IF-band signal quadrupling by the DPMZM was successful. If the IF signal with a higher center frequency and wider bandwidth can be applied to the DPMZM using a state-of-the-art AWG, the center frequency and the bandwidth of the quadrupled signal can be higher and wider, similar to previous studies in References [11,12,[21][22][23].…”
Section: Experimental Setup and Resultssupporting
confidence: 63%
“…Therefore, in order to prevent the generation of thermal noise, an additional cooling system is required, which results in increasing the volume of the system [14][15][16][17]. For these reasons, the previous studied of the photonic-based pulsed radars with an MLL is mainly focused on for long-range target detection, and the acquisition of high-resolution ISAR images has been studied in photonic-based FMCW radars with a CW laser source [8,9,[18][19][20][21][22][23][24]. According to the results of the previous studies, the photonic-based pulsed radar with MLL can replace the conventional electronic-based shipborne radar or airborne radar, and the photonic-based FMCW radar with CW laser can be applied to automobiles, distance measurement, or missile fuses.…”
Section: Introductionmentioning
confidence: 99%
“…With this scheme, a dual-band LFM radar signal (18∼22 GHz, 28∼32 GHz) was produced based on a low-frequency electrical dual-band signal (4.5∼5.5 GHz, 7∼8 GHz) [160]. Thanks to the high quality and high stability of the generated signal, several ultrahighresolution imaging radars were built based on this method [147], [217], [218], [224]- [228].…”
Section: B Photonic Radar Waveform Generationmentioning
confidence: 99%
“…Most of the currently reported optoelectronic hybrid radars for high-resolution imaging are realized through de-chirping processing, where an LFM signal is used as the radar waveform [32], [217], [218], [222], [224]- [228], [323], [375]- [379]. The principle of de-chirp processing of the LFM signal is illustrated in Fig.…”
Section: A Optoelectronic Hybrid Radarmentioning
confidence: 99%
See 1 more Smart Citation